Socialization and education on designing an automatic chili plant watering system in Kota Pari Village - Nasution, Darmeli; Sulistianingsih, Indri; Akbar, Ahmad; Fernando, Ahmad (International Conference on Sciences Development and Technology, 2023)
This service activity aims to provide outreach and education to the people of Kota Pari Village about the design of an automatic chili plant watering system. This system was designed with the aim of increasing agricultural efficiency and productivity, especially in chili cultivation. Through this activity, it is hoped that the public can understand and apply the concepts and working principles of automatic watering systems in agriculture. The activity began with outreach to the public about the benefits and working principles of automatic watering systems as well as the potential for increasing agricultural yields that can be achieved through the use of this technology. Next, practical education was carried out regarding the installation and use of an automatic watering system for chili plants. Participants will be given a step-by-step guide in installing and operating an automatic watering system. Apart from that, this activity also involves direct assistance and monitoring of the implementation of the automatic watering system in the community's chili plants. The service team will assist in overcoming obstacles that may arise and provide direction and suggestions in using the system. Through this outreach and education activity, it is hoped that the people of Kota Pari Village can utilize and adopt automatic watering system technology to increase their agricultural yields. With this system, it is hoped that the efficiency of water use and labor can increase, so that the productivity and quality of chili plants can be improved.